Factores biosicosociales y nivel de autoestima del adulto mayor centro del adulto mayor essalud Chepen 2010 - Cubas Lopez, Margot Barbarita (2010)
The present work of investigation of descriptive type and of transverse court, it was realized by the intention of determining the relation that exists between the factors biopsychosocial: Age, sex, conjugal condition, participation in recreational activities and intrafamilial relations with the level of auto esteem in the major adult. The sample was shaped by 233 major adults, resident adults in Chepén, selected randomly, for the information compilation were used the instruments on the biopsychosocial factors of the major adult and the scale of valuation of the level of autoesteem of major adult, elaborated by the authoresses, on the basis of studies of Vásquez (1994), Méndez (1997), Rosemberg (1998), Castle (1998), respectively and applied to the major adult, considering the ethics, this is anonymity and confidentiality. The information was tabulated manually and presented in statistical pictures of simple and double entry. For the statistical analysis we apply the Test of Independence of Criterion Square Chi. The analysis and discussion of the results have the following conclusions: The mayority of the major adults present a high baju of autoesteem 54.94 %. It was found significant influence between the autoesteem and the participation in recreational activities, as well as with the intrafamilial relations.